FLEXURAL CHARACTERISTICS OF ROLL-WRAPPED GFRP COMPOSITE HOLLOW SQUARE TUBE - Priyanto, Kaleb; Haniel, Haniel; Palmiyanto, Martinus Heru; Priyambodo, Bambang Hari (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
This research characterizes the bending behavior of hollow square tube glass fiber-reinforced polymer (GFRP) composites using the roll-wrapping method. CSM (Chopped Strand Mat) and WRM (Woven Roving Mat) glass fibers were chosen as reinforcing constituents with epoxy as the matrix. Glass fiber was chosen because it has strength, stiffness, lightness, corrosion resistance and high-temperature resistance. These properties can be utilized for frame and structural applications in various types of transportation equipment. The roll-wrapping technique was chosen for manufacturing GFRP composite hollow square tubes. The roll-wrapping technique is the simplest method and does not require a lot of money. The bending test using the Three Point Bending method is based on the ASTM D7264 test standard. In addition, macroscopic observations of the specimen's cross-section after experiencing a bending load are carried out to determine the product failure criteria. Bending tests were conducted on two types of GFRP composites, hollow square tube products produced from CSM and WRM fibers. The bending test results showed that the CSM fiber-reinforced composite has higher stress values (167.122 MPa) and strain (0.055%) compared to the WRM fiber-reinforced composite, which has stress values of 78.339 MPa and strain of 0.030%. The results of macro photo analysis show that random fiber composites dominate tensile failure while woven fiber composites dominate compressive failure. Failure analysis through macro photos is a critical process in determining the physical root cause of the problem